Transmission error monitoring method of hydraulic excavating machinery based on M/T algorithm - Chen, Fang (Frontiers in Mechanical Engineering, 2025)
IntroductionAccurate speed measurement is crucial for improving the efficiency and reliability of the transmission system in hydraulic excavators. However, traditional M and T methods have their own limitations in speed measurement, especially in terms of measurement accuracy over a wide speed range.MethodsA M/T velocity measurement algorithm combining the advantages of M and T methods was proposed to address this issue, and dynamic errors were obtained. The kinetic energy theorem can also be used.ResultsThe experimental results show that under the normal load of unit tooth width F, the change rate of transmission error is less than 5% and less than 2% nM > 100N/mm.DiscussionThe monitoring method of hydraulic excavating mechanical transmission error has the advantages of high accuracy and strong adaptability, which can provide a new highway bureau for mechanical transmission error monitoring.